The Corelation of Compliance to Use PPE (Mask) and The Event of Respiratory Disorders in Workers in Bukit Kapur Jaddih, Parseh Village, Socah District, Bangkalan Regency - Ervi Suminar; Nurun Nikmah; Levi Tina Sari; Wahyu Wibisono (STIKes Patria Husada Blitar, 2021)
The process of limestone mining will resulted in limestone dust on the working environment. This can lead to inhalation of the limestone dust which can cause respiratory problems.The type of the research was analytic with Cross Sectional design. The population was all workers in Bukit Kapur Jaddih, Parseh Village, Socah District; 52 workers. The sample was 45 workers taken by simple random sampling technique. The independent variable was compliance to use mask protective equipment, while the dependent variable was respiratory disorders. The data was collected by questionnaires and observation physical observation. Â The data was analyzed using Lambda test, with Î±= 0.05.The results of the research showed that workers who did not use PPE (masks) were 35 workers (77.8%), who experienced respiratory problems were Â 39 workers (86.7%), and 6 workers (13.3%) did not experience respiratory problems. The lambda test results p Value of 0.073>Î± (0.05) meant that H0 was accepted and H1 was rejected. The compliance to use personal protective equipment (masks) and the presence of respiratory problems showed no correlation. For this reason, workers must continue to use masks while working to protect themselves from the effects of occupational breathing (lime dust).